2017
DOI: 10.1159/000455930
|View full text |Cite
|
Sign up to set email alerts
|

Modified Fluorodeoxyglucose Metabolism in Motor Circuitry by Subthalamic Deep Brain Stimulation

Abstract: Background: Adjustment of the motor circuitry has been described in the treatment of Parkinson disease (PD). Objectives: To evaluate the modulation of the motor circuitry of PD patients by subthalamic deep brain stimulation (STN DBS) using 18F-fluorodeoxyglucose (FDG) and positron emission tomography (PET). Methods: Resting-state brain 18F-FDG PET imaging was performed for 8 PD patients before surgery and also 1 year after STN DBS treatment; changes in regional glucose metabolism were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…After 1 year STN DBS treatment, Cao et al . () found ‘pronounced elevations (activation) in parietal and occipital glucose’ plus ‘an obvious reduction in caudate, putamen, cerebellum, and frontal cortex glucose metabolism’.…”
Section: Mechanisms Of Action Of Dbs: a Brief Excursusmentioning
confidence: 99%
“…After 1 year STN DBS treatment, Cao et al . () found ‘pronounced elevations (activation) in parietal and occipital glucose’ plus ‘an obvious reduction in caudate, putamen, cerebellum, and frontal cortex glucose metabolism’.…”
Section: Mechanisms Of Action Of Dbs: a Brief Excursusmentioning
confidence: 99%
“…In general, connectivity with subcortical areas (thalamus, midbrain, pons) is diminished, whereas both decreases and increases for different cortico-striatal connections have been reported (Hacker et al, 2012; Hou et al, 2016; Manza et al, 2016). Conflicting results about the effects of STN-DBS emerged from imaging studies: some authors reported STN-DBS-related activations of the striatum (Geday et al, 2009; Hilker et al, 2004; Knight et al, 2015; Stefurak et al, 2003), whereas others found deactivations (Cao et al, 2017; Le Jeune et al, 2010). The impact of STN-DBS on striatal connectivity is entirely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, our analysis revealed that this sweet spot, described with relatively high consistency in the literature, might correspond to the SMA cluster. SMA glucose utilization, and hence activity, has been shown to be decreased as an effect of DBS for PD [30].…”
Section: Discussionmentioning
confidence: 99%